S16 The influence of the CFTR modulator ivacaftor on aspergillosis in cystic fibrosis. (12th November 2019) - Fritsch, NC; Green, HD; Jones, AM; Barry, PJ
Abstract : Introduction: Cystic fibrosis (CF) is a life limiting genetic condition which occurs due to mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR). Absence of functional CFTR protein leads to progressive respiratory disease characterized by bronchiectasis and chronic infections. CF lung disease predisposes patients to infection and sensitivity to the fungal pathogen Aspergillus fumigatus. Novel CFTR modulating therapies have recently been associated with potential disease modification in CF. It is unclear whether these therapies will have an influence on susceptibility to Aspergillus related disease in CF. Methods: We conducted a retrospective cohort study examining patients who commenced the CFTR modulator ivacaftor. Over a period of 5 years we monitored the isolation ofAspergillus in sputum samples and patients' serological response to Aspergillus fumigatus. Results: In 40 patients, ivacaftor therapy resulted in a significant decrease in sweat chloride (from 112 [102.75 – 119.25] to 45 [37 – 61], p<0.001), and an increase in FEV1 from 53.2% to 63.1% predicted. One patient was treated both with CFTR modulators and itraconazole for ABPA. There was a significant decrease in the number of sputum samples patients provided in the year preivacaftor initiation compared to 5 years post from a median of 7 [4 – 12.75] per year to 1 [0 – 4], p<0.001. There was no difference in the rate of Aspergillus isolation in sputum. There was an early decrease (at 6 months) in total IgE levels from 35.55 [15.9 – 202.5] to 26.7 [9.5 – 108.25] (p=0.02) but these were not sustained over longer periods. There were no significant changes in Aspergillus specific IgE or IgG over the study time. Conclusion: Effective CFTR modulation in patients with CF does not appear to alter susceptibility or reaction to Aspergillus fumigatus in clinical settings. These findings suggest that Aspergillus will remain a significant pathogen in a new era of CF when most patients will receive CFTR modulator therapy. This will potentially result in clinical challenges due to difficult drug-drug interactions between –azole medications and CFTR modulators.